Inactivation of bacteria via photosensitization of vitamin K3 by UV-A light. Issue 1 (1st September 2014) - Xu, Fei; Vostal, Jaroslav G.
Abstract: This study investigated inactivation of bacteria with ultraviolet light A irradiation in combination with vitamin K3 as a photosensitizer. Six bacteria including Bacillus cereus, Pseudomonas aeruginosa, Staphylococcus aureus, Staphylococcus epidermidis, Klebsiella pneumoniae, and Escherichia coli suspended in vitamin K3 aqueous solution were exposed to ultraviolet light A. Five of six bacteria, with the exception of Pseudomonas aeruginosa, were reduced by eight logs with 1600 μM of vitamin K3 and 5.8 J cm −2 UV-A irradiation. Pseudomonas aeruginosa was reduced by four logs under these conditions. Reactive oxygen species including singlet oxygen, hydroxyl radical and superoxide anion radical were generated in vitamin K3 aqueous solution under UV-A irradiation. These results suggest that vitamin K3 and UV-A irradiation may be effective for bacterial inactivation in environmental and medical applications. Abstract : A combination of UV A light and Vitamin K3 is highly effective for bacterial inactivation. Abstract :